Fundamental measure theory for smectic phases: Scaling behavior and higher order terms - Wittmann, Rene; Marechal, Mattheus; Mecke, Klaus (Journal of Chemical Physics, 2014)
The recent extension of Rosenfeld's fundamental measure theory to anisotropic hard particles predicts nematic order of rod-like particles. Our analytic study of different aligned shapes provides new insights into the structure of this density functional, which is basically founded on experience with hard spheres. We combine scaling arguments with dimensional crossover and motivate a modified expression, which enables an appropriate description of smectic layering. We calculate the nematic-smectic-A transition of monodisperse hard spherocylinders with and without orientational degrees of freedom and present the equation of state and phase diagram including these two liquid crystalline phases in good agreement with simulations. We also find improved results related to the isotropic-nematic interface. We discuss the quality of empirical corrections and the convergence towards an exact second virial coefficient, including higher order terms. (C) 2014 AIP Publishing LLC.